A Possible Link between Infection with Burkholderia Bacteria and Systemic Lupus Erythematosus Based on Epitope Mimicry. (9th July 2008) - Zhang, Wei; Reichlin, Morris
Abstract : We previously demonstrated that purified polyclonal and monoclonal anti-dsDNA antibodies bind a 15-mer peptide ASPVTARVLWKASHV in ELISA and Dot blot. This 15-mer peptide partial sequence ARVLWKASH shares similarity with burkholderia bacterial cytochrome B 561 partial sequence ARVLWRATH. In this study, we show that purified anti-dsDNA antibodies react with burkholderia fungorum bacterial cell lysates in Western blot. We used anti-dsDNA antibodies to make an anti-dsDNA antibodies affinity column and used this column to purify the burkholderia fungorum bacterial protein. Purified anti-dsDNA antibodies bind specifically to purified bacterial antigen and purified bacterial antigen blocked the anti-dsDNA antibodies binding to dsDNA antigen. Sera with anti-dsDNA antibodies bind specifically to purified bacterial antigen. We obtained protein partial sequence of RAGTDEGFG which is shared with burkholderia bacterial transcription regulator protein sequence. Sera with anti-dsDNA antibodies bind to RAGTDEGFG peptide better than control groups. These data support our hypothesis that the origin of anti-dsDNA antibodies in SLE may be associated with burkholderia bacterial infection.